The Contribution of Islamic Boarding Schools to the Character Building of Indonesian Society - Eko Nani Fitriono (Mau`izhah : Jurnal Kajian Keislaman, 2022)
Throughout the establishment in Nusantara (Nation), Islamic boarding school has exclusivity in building the santri (students) character as a provision in the future society life. Starting from traditional, modern, and comprehensive Islamic boarding schools, all of them try to build the character of Indonesia society. The three Islamic boarding school models provide idea that Islamic boarding school, in this case, is an Islamic educational institution that runs and develop according to current development. Dimensions of the education system activities performed by Islamic boarding school have the main purpose, namely to change human character to be better, both individually or collectively. Therefore, indirectly, Islamic boarding school has actually become a place for character building through its exclusive educational models. Indonesian government in the efforts to realize character education can make Islamic boarding school as the model to be implemented in the existing education. In this case, Islamic boarding school managed to integrate religion and morality values as part of understanding all existing knowledge. Therefore, Islamic boarding school is an original character education model, in which religious values are the reference in building perfect human character.